2015
DOI: 10.1002/pros.23002
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin as a potential tumor suppressor inhibiting epithelial‐to‐mesenchymal transition but frequently silenced in prostate cancer by promoter methylation

Abstract: Our findings indicated that endogenous ADN may function as a tumor suppressor gene through inhibiting EMT of PCa cells but is down-regulated in PCa via promoter hypermethylation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 35 publications
1
25
0
6
Order By: Relevance
“…Cells tend to have stronger replicative capacity in the condition of adiponectin deficiency, this capacity is limited and controllable. Although several studies have found correlative evidence between adiponectin deficiency and cancers25, including breast cancer42, hepatocellular carcinoma43 and prostate cancer44. Additional studies are needed to determine whether adiponectin deficiency contributes to the limitless replicative potential of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Cells tend to have stronger replicative capacity in the condition of adiponectin deficiency, this capacity is limited and controllable. Although several studies have found correlative evidence between adiponectin deficiency and cancers25, including breast cancer42, hepatocellular carcinoma43 and prostate cancer44. Additional studies are needed to determine whether adiponectin deficiency contributes to the limitless replicative potential of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…+/− [107,151] Funding: This work was supported by grants from the Ministero della Salute (Ricerca Corrente L4084, 2016; L4101, 2017).…”
Section: Breast Cancer Progress Leptin Adiponectin Sam68mentioning
confidence: 99%
“…Bub et al showed that adiponectin was a growth inhibitor in PCa cells [34]. Further findings indicated that endogenous adiponectin functioned as a tumor suppressor through inhibiting epithelial-to-mesenchymal transition of PCa cells [35]. On the other side, some researchers presented negative results, suggesting that adiponectin may not play an important role in promoting clinically aggressive PCa [36,37].…”
Section: Discussionmentioning
confidence: 95%